2008
DOI: 10.1007/s10228-008-0059-9
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in foraging tactics of the piscivorous cornetfish Fistularia commersonii

Abstract: Foraging behaviors of the piscivorous cornetfish Fistularia commersonii were observed at shallow reefs in Kuchierabu-jima Island, southern Japan. This fish foraged on two types of prey fishes: one was reef fish that typically dwell on or near substrata (e.g., Tripterygiidae and Labridae), and the other was pelagic fish that shoal in the water column (e.g., Clupeidae and Carangidae). The prey sizes, prey types and foraging behaviors changed as the predator size increased. Prey sizes were largely limited by gape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
2
19
0
1
Order By: Relevance
“…For example, as juvenile Walleye grow, more prey are consumed due to behavioral developments in foraging behavior . Similarly, small Reef Cornetfish Fistularia commersonii (<30 cm TL) in the field mainly stalk benthic fish and have short attack distances, but larger fish forage on pelagic as well as benthic prey using chasing and associative foraging tactics (Takeuchi 2009). In prey vulnerability experiments, juvenile Largemouth Bass showed few ontogenetic changes in foraging behavior with size, even though prey morphology and behavior changed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as juvenile Walleye grow, more prey are consumed due to behavioral developments in foraging behavior . Similarly, small Reef Cornetfish Fistularia commersonii (<30 cm TL) in the field mainly stalk benthic fish and have short attack distances, but larger fish forage on pelagic as well as benthic prey using chasing and associative foraging tactics (Takeuchi 2009). In prey vulnerability experiments, juvenile Largemouth Bass showed few ontogenetic changes in foraging behavior with size, even though prey morphology and behavior changed.…”
Section: Discussionmentioning
confidence: 99%
“…Significant numbers of adults were also occasionally found, leading to their classification as seagrass residents. Several studies have shown that F. commersonii ontogenetically shift towards more generalist feeding and habitat selection (Bilecenoglu et al , 2002; Takeuchi et al , 2002; Kalogirou et al , 2007; Bariche et al , 2009; Takeuchi, 2009). Lagocephalus sceleratus ranked among the 10 most dominant fish species in terms of biomass, a pattern resulting from the capture of a few large specimens during winter.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between multidimensionality and host diversity may eventually be tested by comparing the extent of multidimensionality in manipulation between parasites with trophic transmission differing in their specificity for final hosts. However, multidimensionality might be beneficial even if the parasite relies on a limited number of species as appropriate final hosts, when, for instance, the predatory behaviour of the latter shows some variation related to age (Graeb et al, 2006;Takeuchi, 2009).…”
Section: Adaptive Explanations For Multidimensionality In Pipasmentioning
confidence: 99%